The acute effect of swimming on airway inflammation in adolescent elite swimmers - Pedersen, L.; Lund, T. K.; Mølgaard, E.; Kharitonov, S. A.; Barnes, P. J.; Backer, V. (Journal of Allergy and Clinical Immunology, 2009)
Elite athletes have been found to have airway inflammation, and endurance sport, in particular, has been suggested to cause inflammation. The number of studies on airway inflammation in elite athletes is limited. Most studies have focused on the long-term effect of elite sport, and only a few studies have examined the acute effect of exercise on airway inflammation. These few studies have mainly considered adult nonelite or elite athletes who have been involved in elite sport for many years and who already seem to have had significant inflammatory changes. It remains uncertain whether exercise increases existing airway inflammation or whether exercise can induce an acute inflammatory process in individuals without airway inflammation. In this study we aimed to evaluate the acute effect of a training session in an indoor swimming pool on airway inflammation in adolescent elite swimmers.